1
$\begingroup$

Please help me to find this indefinite integration

$$\int\sqrt\frac{1}{x^3-1}~dx$$

I guess, this is an indefinite integral. Do you have a tip for me to solve this ? Thank you in advance!

$\endgroup$
  • 2
    $\begingroup$ Possibly not easy $\endgroup$ – Henry Jan 13 '17 at 20:04
  • 3
    $\begingroup$ There's no hope for an easy answer here. The anti-derivative involves elliptic integrals. My advice: Just move along. Nothing to see here. $\endgroup$ – B. Goddard Jan 13 '17 at 20:08
  • $\begingroup$ How can I calculate this indefinite integral: ∫ √ 1 x3−1 dx $\endgroup$ – addicted.insta Jan 14 '17 at 6:33
1
$\begingroup$

Case $1$: $|x|\leq1$

Then $\int\sqrt{\dfrac{1}{x^3-1}}~dx$

$=\int\dfrac{1}{(x^3-1)^\frac{1}{2}}~dx$

$=\int\dfrac{1}{i(1-x^3)^\frac{1}{2}}~dx$

$=-i\int\sum\limits_{n=0}^\infty\dfrac{(2n)!x^{3n}}{4^n(n!)^2}~dx$

$=-\sum\limits_{n=0}^\infty\dfrac{i(2n)!x^{3n+1}}{4^n(n!)^2(3n+1)}+C$

Case $2$: $|x|\geq1$

Then $\int\sqrt{\dfrac{1}{x^3-1}}~dx$

$=\int\dfrac{1}{(x^3-1)^\frac{1}{2}}~dx$

$=\int\dfrac{1}{x^\frac{3}{2}(1-x^{-3})^\frac{1}{2}}~dx$

$=\int\sum\limits_{n=0}^\infty\dfrac{(2n)!x^{-3n-\frac{3}{2}}}{4^n(n!)^2}dx$

$=\sum\limits_{n=0}^\infty\dfrac{(2n)!x^{-3n-\frac{1}{2}}}{4^n(n!)^2\left(-3n-\dfrac{1}{2}\right)}+C$

$=-\sum\limits_{n=0}^\infty\dfrac{(2n)!}{2^{2n-1}(n!)^2(6n+1)x^{3n+\frac{1}{2}}}+C$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.